1983
DOI: 10.1007/bf00285389
|View full text |Cite
|
Sign up to set email alerts
|

Virus-induced gene mutations of eukaryotic cells

Abstract: Most animal viruses studied so far induce chromosomal aberrations. In addition, adenoviruses, papovaviruses, and retroviruses are known to induce gene mutations like mutagenic bacteriophages. At least in one case studied retrovirus induced mutagenesis involves gene and/or scripton splitting analogous to the mutagenic mechanism of action of mutatorphage Mu and other movable DNA elements. On the contrary, several results obtained by independent means indicate that Simian virus 40, a papovavirus, does not act by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…A related hit-andrun mechanism is probably responsible for herpes simplex virus transformation. All human herpesviruses induce chromosomal aberrations (19,33) and recent work has shown that the transforming sequences of herpes simplex virus types 1 and 2 and of cytomegalovirus contain DNA sequences with structural characteristics similar to insertion-sequence elements (34). Restriction enzymes that cut within these elements destroy the transformation activity, possibly by preventing their action as insertion sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A related hit-andrun mechanism is probably responsible for herpes simplex virus transformation. All human herpesviruses induce chromosomal aberrations (19,33) and recent work has shown that the transforming sequences of herpes simplex virus types 1 and 2 and of cytomegalovirus contain DNA sequences with structural characteristics similar to insertion-sequence elements (34). Restriction enzymes that cut within these elements destroy the transformation activity, possibly by preventing their action as insertion sequences.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of chemical hepatocarcinogenesis in the mouse and rat, agents that damage DNA stimulate the occurrence of HCC (15)(16)(17)(18). The ability of oncogenic viruses to damage DNA through integration and by increasing the mutation rate of cellular genes is probably an important factor in virusmediated multistage carcinogenesis (19). To investigate the possible role of HBV integrations in a general mechanism involving host DNA rearrangements, we have studied the structure of cellular DNA sequences at HBV integration sites.…”
mentioning
confidence: 99%
“…Such an outcome can be reasonably explained with variants of residual HPRT enzyme activity caused by mutations in different loci of the HPRT gene [37]. Earlier results on SV40-induced mutagenesis led to the conclusion of point mutations having occurred in the majority of TG r mutants, were compatible with the assumption of a structurally altered enzyme dihydrofolate reductase in antifolate drug resistant mutants, or were interpreted by base exchange mutations having led to Oua resistance [11,38]. But other types of mutations shown to cause these kinds of drug resistance too [20,32,43] might also be involved.…”
Section: Discussionmentioning
confidence: 93%
“…The combined action of both mutagens resulted in a mutant production in V79 cells much exceeding the sum of mutants produced by single treatments (Table 1). Therefore, in BKV-infected mammalian cells virus-induced mutations are detectable in dependence on the viral dose, the operative mutation expression time and possible synergistic effects elicited by combined action of the virus and another mutagen -findings that seem to be analogous to effects described earlier for the simian papovavirus SV40 [11]. [7,47] it seemed to be intersting to c o m p a r e the mutagenic effects o f wild-type virus and B K V -I R , a virus variant isolated from a h u m a n t u m o r and bearing b o t h an insertion and a deletion in the early region o f the genome [27].…”
Section: Mutagenic Activity Of Bkv and Jcvmentioning
confidence: 88%
See 1 more Smart Citation